Covalently Linked 5, 15‐Diazaporphyrin Dimers: Promising Scaffolds for a Highly Conjugated Azaporphyrin π System. Issue 12 (12th February 2014) - Matano, Yoshihiro; Fujii, Daisuke; Shibano, Tarou; Furukawa, Ko; Higashino, Tomohiro; Nakano, Haruyuki; Imahori, Hiroshi
Abstract The first examples of β–β directly linked, acetylene‐bridged, and butadiyne‐bridged 5, 15‐diazaporphyrin dimers have been prepared by palladium‐catalyzed coupling reactions of nickel(II) and copper(II) complexes of 3‐bromo‐10, 20‐dimesityl‐5, 15‐diazaporphyrin (mesityl=2, 4, 6‐trimethylphenyl). The effects of the linking modes and meso‐nitrogen atoms on the structural, optical, electrochemical, and magnetic properties of the distributed π systems were investigated by using X‐ray crystallography, UV/Vis absorption spectroscopy, DFT calculations, cyclic voltammetry, and ESR spectroscopy. Both the electronic and steric effects of the meso‐nitrogen atoms play an important role in the highly coplanar geometry of the directly linked dimers. The direct β–β linkage produces enhanced π conjugation and electron‐spin coupling between the two diazaporphyrin units.